2000
DOI: 10.1002/1097-4555(200011)31:11<1029::aid-jrs640>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental vibrational study of polyaniline in base forms: non-planar analysis. Part I

Abstract: Experimental and theoretical studies of basic forms of polyaniline are presented. Experimental spectra of emeraldine, leucoemeraldine and pernigraniline and their oligomer model compounds (diphenylamine, phenyl‐end‐capped dimer, phenyl‐end‐capped tetramer, phenyl‐end‐capped hexamer, imine form of phenyl‐end‐capped dimer, pernigraniline base phenyl‐end‐capped tetramer and emeraldine base phenyl‐end‐capped tetramer) were recorded in N‐methyl‐2‐pyrrolidone solution and in the solid state. The calculations were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 38 publications
4
70
0
1
Order By: Relevance
“…From the recorded spectrum of PANI-EB (Fig. 2b) one can observe the characteristic peak at 1593 cm -1 , which is due to the C=C stretching in the quinoid ring, the 1378 cm -1 peak typical for C-N stretching [22][23][24].…”
Section: Characterizationmentioning
confidence: 91%
“…From the recorded spectrum of PANI-EB (Fig. 2b) one can observe the characteristic peak at 1593 cm -1 , which is due to the C=C stretching in the quinoid ring, the 1378 cm -1 peak typical for C-N stretching [22][23][24].…”
Section: Characterizationmentioning
confidence: 91%
“…However, it was often observed that the quality of the products such as the shape and stability of their dispersions varies with different synthetic conditions, such as, stirring, temperature and pH, among others. (Colomban et al, 1999;Cochet et al, 2000a;Cochet et al, 2000b) have been demonstrated that the low energy Raman bands from 100 to 600 cm -1 in the PANI spectra are very sensible to the crystalline arrangement and also to the conformational changes of the PANI chains. The Raman spectra of PANI nanofibers prepared from interfacial polymerization were obtained at low wavenumbers.…”
Section: Pani Nanofibers Obtained From Interfacial Polymerizationmentioning
confidence: 98%
“…In addition, shifts of the bands from 393-427 cm -1 to 422-451 cm -1 are also seen for PANI nanofibers prepared with higher HCl concentration. (Cochet et al, 2000a;Cochet et al, 2000b) demonstrated that mainly the bands at about 200-500 cm -1 are very sensible to the conformational changes. The shift to higher wavenumbers of the bands at about 400 cm -1 indicates the increase of the torsion angles of the C ring -N-C ring segments.…”
Section: Pani Nanofibers Obtained From Interfacial Polymerizationmentioning
confidence: 99%
“…Alguns picos Raman característicos da POMA-ES são: 577 cm -1 atribuído à deformação da amina no plano, 1356 cm -1 atribuído ao cátion radical (estiramento C-N + ) e 1597 cm -1 atribuído ao estiramento C-C do anel benzeno. A Tabela 1 traz os picos Raman da base e do sal de POMA esmeraldina, e suas respectivas atribuições, as quais são "atribuições tentativas" baseadas nas referências [30][31][32][33][34][35] que se referem à PANi.…”
Section: Caracterização Vibracional E Morfológica Por Microespectroscunclassified